A Rare Twist of the Forgotten Disease: A Case of Fusobacterium necrophorum Sepsis with Portomesenteric Thrombosis and a Review of the Literature - Nicholas Lazar; Kamil Sardarli; Zaid Imam; Majd Khasawneh; Ismail Hader (Case Reports in Gastrointestinal Medicine)
Abdominal variants of Lemierre’s syndrome presenting with pylephlebitis are rare, and the role of anticoagulation in treatment is controversial. We hereby report a case of pylephlebitis secondary to F. necrophorum bacteremia in a 57-year-old female originating from bacterial translocation secondary to colitis, who developed a favorable outcome with prompt treatment with antibiotics and anticoagulation. We also perform a literature review on similar cases in the literature and discuss management options of this rare but potentially fatal complication.